The Association Between Dairy Product Consumption and Asthenozoospermia Risk: A Hospital-Based Case-Control Study - Wang, Xiao-Bin; Wu, Qi-Jun; Liu, Fang-Hua; Zhang, Shuang; Wang, Han-Yuan; Guo, Ren-Hao; Leng, Xu; Du, Qiang; Zhao, Yu-Hong; Pan, Bo-Chen (Frontiers in Nutrition, 2021)
Background Evidence of an association between dairy product and related nutrient intake, and the asthenozoospermia risk have been limited and controversial. Methods A case-control study including 549 men with asthenozoospermia and 581 healthy controls interviewed in the infertility clinics of Shengjing Hospital of China Medical University between June, 2020 and December, 2020. Dietary intake was assessed with a validated food frequency questionnaire, and semen parameters were analyzed according to the World Health Organization guidelines. The daily intake of dairy products and related nutrients was categorized into three groups, and the lowest tertile was used as the reference category. An unconditional multiple logistic regression was used to estimate the odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) for asthenozoospermia risk. Results After adjustment for potential confounders, we found no statistically significant associations between the intake of total dairy and asthenozoospermia risk (ORT3vs.T1=1.14, 95%CI=0.80–1.58). Additionally, we generated null findings regarding the main related nutrients from dairy, including protein (ORT3vs.T1=1.14, 95%CI=0.82–1.59), fat (ORT3vs.T1=1.23, 95%CI=0.88–1.71) and calcium (ORT3vs.T1=1.15, 95%CI=0.83–1.60), and asthenozoospermia risk. Of note, after stratification by body mass index (BMI), and the fat consumption from dairy was significantly associated with a higher asthenozoospermia risk (ORT3vs.T1=1.77, 95%CI=1.03–3.06) among participants with a BMI below 25 kg/m2. Conclusion This study provided limited evidence of an association between the intake of total dairy, protein, fat, and calcium, and the asthenozoospermia risk. Further studies are warranted to confirm our findings in the future.